Islamic banking interest free banking scheme, Islamic concepts and comparison among the conventional bank / Mohd Fikri Ispal - Ispal, Mohd Fikri (1997)
Today banking system has been one step future since it implement 2 banking system, which is consist of the Conventional Banking System and the Interest Free Banking System. These studies will be only focus on the IFBS, since we know the IFBS have been officially implemented on 4 March 1993, until then the participant among the financial institution has increase to 49. This includes 25 commercial banks, 21 finance companies and 3 merchant banks. The IFBS counter is under the Bank Negara Malaysia Syariah supervisor. The studies also attempt to examine the performance of the selected financial institution base on four variables. These include the total amount deposit, the total number depositor, total number of branches and inflation rate. In analysis the data, Multiple Regression Method is used for each financial institution, which was selected.